Grand multiparity and obstetric complications at the federal medical centre Umuahia, Abia State, Nigeria: a case control study - C., Okoye Clara; J., Nnamdi Nneka; G., Eluwa Chidinma; N., Nwachukwu Norah; O., Udoinyang Florence (International Journal of Research in Medical Sciences, 2026)
Background: Maternal mortality associated with multiparity increases steadily and speedily from the fifth pregnancy till the tenth or more with a mortality rate five times as high as in all women bearing children. Methods: It was a five-year case controlled retrospective study of grand multiparous and multiparous women who presented at the hospital between January 1st, 2010 and 31st December, 2014. The population of the study consisted of 136 booked grand multiparous and 136 booked multiparous women who received antenatal, intranatal and postnatal care at the hospital during the period of the study. The entire population was used. The instruments for data collection were the obstetrics records and registers and the individual patient’s case notes that were obtained from the Medical Records Department and from labour ward of the Federal Medical Centre (F.M.C) Umuahia. Data were collected using researcher’s developed proforma and were analysed descriptively using SPSS/IBM version 20 and presented in frequencies, percentages, means and standard deviation. A chi-square test was used for comparison of data which was taken at p 0.05. Results: The major findings showed that anaemia, chronic hypertension, antepartum haemorrhages, postdate, macrosomia, postpartum haemorrhage etc. were higher in the grand-multiparas compared to the multiparas. Multiparas had higher incidence of pre-eclampsia, caesarean section, low birth weight etc. than the grand-multiparas. Conclusions: It is recommended that there is need to encourage female child education and equip obstetric facilities adequately to reduce the complications resulting from grand-multiparity.